Forced convection of flow past two tandem rectangular cylinders in a channel. (3rd July 2017) - Zhang, Wei; Yang, Hui; Dou, Hua-Shu; Zhu, Zuchao
ABSTRACT: This work performed the first numerical investigation on the forced convection of flow past two tandem rectangular cylinders in a channel at Re = 100. The aspect ratio (AR) and gap ratio (GR) of the two cylinders are chosen at AR = 1(1)4 and GR = 1(1)8, respectively. The objective of the present work is to explore the effects of AR and GR on the characteristic flow and heat transfer quantities for the rectangular geometry that has not been studied before. The effects of the two parameters are presented by the instantaneous flow pattern, characteristic aerodynamic and heat transfer quantities, local heat transfer rate, flow patterns in the gap and near wake, and temperature distribution on the channel walls. Both time-averaged and fluctuating quantities are analyzed and presented. Numerical results reveal that for cylinders of all ARs, there are two flow regimes categorized based on the GR: the steady flow regime at GR  ≤ 3, where the gap flow is steady, and the unsteady flow regime at GR ≥ 4. The characteristic aerodynamic and heat transfer quantities abruptly change as the flow transits from steady to unsteady regime especially for the downstream cylinder. The time-averaged and maximum fluctuating local heat transfer rate for the upstream cylinder almost does not vary with the GR, whereas they substantially vary for the downstream cylinder. The AR affects the magnitude of the quantities but not their variation trends. For flows in the unsteady regime, the recovery of the wake flow after the downstream cylinder is much more rapidly than those of steady flows due to the acceleration arising from the instability brought by the incoming shedding vortices. The violent shedding also effectively enhances heat transfer and increases the temperature of the channel walls.